2018
DOI: 10.22159/ijpps.2018v10i1.21797
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antimicrobial Activity of Lawsonia Inermis and Indigo Tinctoria Against Clinically Isolated Microorganisms

Abstract: Objective: The present study aimed at evaluating the natural antimicrobial activity of Lawsonia inermis (L. inermis) and Indigofera tinctoria (I. tinctoria) against a reference and pathogenic clinically isolated strains compare with some antibiotics. Methods:The antimicrobial activity of Lawsonia inermis (red henna) and Indigo tinctoria (black henna) was evaluated against clinically isolated strains from urinary tract and wounds infected patients. The six tested strains namely were Staphylococcus aureus, Enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…Based on this fact, we studied the antibacterial properties of the extract obtained from the leaves of this plant. Our observations show that the extract from I. tinctoria has negligible antibacterial activity relative to the reference and hospital strains of S. aureus, P. aeruginosa and did not affect E. coli and K. pneumoniae strains, which corroborates the results of a study by some authors [61,62] but is not consistent with the data of other researchers who demonstrated antimicrobial activity of I. tinctoria extracts [63] against S. aureus, E. faecalis, K. pneumoniae, Enterobacter aerogenes, and Salmonella paratyphi [64].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Based on this fact, we studied the antibacterial properties of the extract obtained from the leaves of this plant. Our observations show that the extract from I. tinctoria has negligible antibacterial activity relative to the reference and hospital strains of S. aureus, P. aeruginosa and did not affect E. coli and K. pneumoniae strains, which corroborates the results of a study by some authors [61,62] but is not consistent with the data of other researchers who demonstrated antimicrobial activity of I. tinctoria extracts [63] against S. aureus, E. faecalis, K. pneumoniae, Enterobacter aerogenes, and Salmonella paratyphi [64].…”
Section: Discussionsupporting
confidence: 78%
“…Henna (L. inermis) leaves have been extensively used for centuries in India and many other Asian and African countries for cosmetic dye and in treating skin problems, headache, jaundice, amebiasis and enlargement of the spleen [75]. However, the opinions of the authors [63,[76][77][78] with regard to its antimicrobial activity differ and do not in all cases agree with the results of our study. There are reports of a high inhibitory ability of its extract against the reference and clinical strains of P. aeruginosa, K. pneumoniae, E. coli and many other etiological agents of purulent inflammatory diseases and pathogens of intestinal infections.…”
Section: Discussioncontrasting
confidence: 56%
“…A previous study reported antibacterial activity of L. inermis against S. pneumoniae ranging from moderate to very strong activity [18]. Another study also reported that Lawsonia inermis aqueous and ethanol extract showed active antibacterial activity (MIC value = 0.125 mg/ml) against S. aureus, P. aeruginosa, Candida albicans [49] and S. epidermidis [19].…”
Section: Discussionmentioning
confidence: 91%
“…Lawsonia inermis Linn. was also reported of having antibacterial activity against S. aureus and P. aeruginosa [18][19][20]. However, there is limited study in the antibacterial activity of Indonesian medicinal plants against S. pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…They rely on the available tradition and herbal drugs from plants to maintain their healthcare requirements [3]. About 20% of plants found in the world had been submitted to pharmaceutical or biological tests and a sustainable number of new antibiotics introduced in the market were obtained from natural or semisynthetic resources [4]. In recent times, researchers have directed their attention towards the observation of herbal medicines based on the hypothesis that plants contain natural and novel substances that can promote health and alleviate illnesses and also improve the quality of life.…”
Section: Introductionmentioning
confidence: 99%